Is Daniel 11:1-19 based on a ptolemaic narrative? - Scolnic, Benjamin (Journal for The Study of Judaism, 2014)
Daniel 11 is considered an exceptional Biblical text because of its interest in and accuracy about historical and political events in the Hellenistic world. A recent theory suggests that the author was a former Seleucid scribe; another theory posits the use of a Ptolemaic propaganda document. The approach here will be inductive, reading out from the text to adduce evidence that the author of Daniel 11 either used or reflected the attitudes of Ptolemaic narrative, not necessarily because he was pro-Ptolemaic but because it suited his anti-Antiochene purpose. © Koninklijke Brill NV, Leiden, The Netherlands.
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/035-586-778-649-478 tex.type: [object Object]
Keywords: Bible; Daniel; Maccabean; Source criticism; dept.jst